Aplikasi Media Pembelajaran Tata Surya Untuk Anak Sekolah Dasar Menggunakan Augmented Reality Berbasis Android : Aplikasi Media Pembelajaran Tata Surya Untuk Anak Sekolah Dasar Menggunakan Augmented Reality Berbasis Android - Sutimin Sutimin; Julius Panda Putra Naibaho; Alex De Kweldju (JISTECH: Journal of Information Science and Technology, 2024)
Along with the development of information technology which continues to move from year after year, many learning methods have been created to support teaching and learning process. Learning media is in the form of learning props. The solar system currently still uses print media, videos and teaching aids another simple one where the teacher is more dominant in explaining and the students are the only ones listening. Methods like this don't hone creativity and grasping power students, plus the limited use of teaching aids, on the other hand their availability the latest technology that can be developed into learning media. Method learning with the support of interesting technology-based media will creating effective learning media to help achieve targets learning. Application of augmented reality in learning materials about The solar system provides innovative learning methods that can create interactive learning communication between teachers and students. Method The research method used is the Research and method Development (R&D) which aims to create applied products. In the process of creating this application, the application development process used at this stage using the waterfall developer model. The method is carried out is to do Augmented Reality with Vuforia and Unity to implement on Android devices. The result achieved was the introduction of the solar system displays objects and information. With the Augmented Solar System application Android-based reality can be useful for visualizing the inner solar system more realistic model shape.